2020
DOI: 10.1515/dx-2020-0019
|View full text |Cite
|
Sign up to set email alerts
|

Examining the patterns of uncertainty across clinical reasoning tasks: effects of contextual factors on the clinical reasoning process

Abstract: AbstractObjectivesUncertainty is common in clinical reasoning given the dynamic processes required to come to a diagnosis. Though some uncertainty is expected during clinical encounters, it can have detrimental effects on clinical reasoning. Likewise, evidence has established the potentially detrimental effects of the presence of distracting contextual factors (i.e., factors other than ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
0
13
0
1
Order By: Relevance
“…These theories emphasize how these interactions not only give rise to mental states such as uncertainty but also provide ways for individuals to regulate these states. 45,46…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These theories emphasize how these interactions not only give rise to mental states such as uncertainty but also provide ways for individuals to regulate these states. 45,46…”
Section: Discussionmentioning
confidence: 99%
“…These theories emphasize how these interactions not only give rise to mental states such as uncertainty but also provide ways for individuals to regulate these states. 45,46 The taxonomy can thus assist efforts to understand and improve the management of medical uncertainty. It can help researchers to more systematically measure the effects of different uncertainty management strategies and to develop new theoretical understandings of uncertainty management as a broader psychological process.…”
Section: Key Capacitymentioning
confidence: 99%
“…These findings are consistent with other research showing that more uncertainty is expressed during clinical reasoning inpatient cases where contextual distractions are present. 13,19 Physicians expressed the greatest uncertainty inpatient cases which contained contextual distractions that stemmed from either the patient (e.g., the complexity of presentation, English proficiency), the physician (e.g., fatigue, expertise, cognitive load), or the environment (e.g., length of consultation, the functionality of the electronic medical record). 13 In our study, we also found the highest number of statements expressing implicit uncertainty inpatient cases where contextual distractions arose from the patients' physical condition or misleading symptoms, i.e., patient 2 with iatrogenic opioid dependence, patient 3 with a history of unnecessary gallbladder removal, and patient 6 with vitamin B1 deficiency after gastric sleeve surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The studies by Abby Konapasky and colleagues provide illustrative examples [57], including an exploration of how contextual factors change the language of diagnosis [58], and how contextual factors change the likelihood of arriving at the correct diagnosis (the phenomenon of context specificity). A study by Divya Ramani and colleagues explores how uncertainty interacts with contextual factors in the clinical reasoning process [59]. Marcia Docherty and colleagues report their initial findings from observing senior ER residents [60].…”
Section: Situativity Can Help Us Understand and Address Diagnostic Ermentioning
confidence: 99%